Electrochemical gradients driven 3D printing of nano-twinned copper structures by direct current dynamic meniscus confined electrodeposition. (September 2021) - Zhang, Xianyun; Yuan, Lifeng; Lei, Yu; Zhang, Yifan; Li, Yanying; Nie, Weiye; Gao, Qingqing; Li, Zhixiang; Sun, Aihua; Liu, Fenghua; Cheng, Yuchuan; Xu, Gaojie; et al.
Highlights: A direct-current electrodeposition mode 3D printing technique for fabricating nano-twinned Cu microstructures. Evaporation and electric field mediated electrochemical gradients is introduced as driving force for the twin formation. The printed nano-twinned Cu structures have excellent mechanical strength. Abstract: Nano-twinned metal microstructures have attracted great attention as promising elements in novel microsystems, but it has not been realized by direct-current electrodeposition processes without additional nonmetallic additives or mechanical stirring. Here, a dynamic meniscus-confined electrodeposition process operated at direct current mode (DC-dMCED) is developed for fabrication of microscale copper objects with high density of nanotwins. It is proposed that the growth of nanotwins in DC-dMCED is driven by electrochemical gradients (ECG), which combines the concentration and electrical gradients. The ECG is finely turned by the relative humidity, applied current, and concentration of H2 SO4, according to the results of finite element analysis. The formation mechanism and mechanical properties of the fabricated copper microstructures were studied in detail. This versatile approach eliminates the possible contamination by additives and integration difficulty of mechanical stirring, which can be used to fabricate nanotwins with ultrahigh purity, and provides a promising platform for metal objects with both excellent mechanical strength and superior electrical conductivity. Graphical abstract: Image, graphical abstract